2003
DOI: 10.1046/j.1474-919x.2003.00193.x
|View full text |Cite
|
Sign up to set email alerts
|

The disproportionate effect of global warming on the arrival dates of short‐distance migratory birds in North America

Abstract: Recent studies have shown that, in response to global climate change, diverse avian taxa are now nesting measurably earlier (< 10 days) in both the United States and Britain. Similarly, several studies on European birds have now demonstrated that a variety of species (although not all) are arriving increasingly early. However, surprisingly, widespread changes in North American migrant phenology have not been demonstrated. It is hypothesized that short‐distance migrants (birds that winter in the southern United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
211
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 220 publications
(246 citation statements)
references
References 26 publications
27
211
8
Order By: Relevance
“…In several species we found a signifi cant correlation between initial capture dates in the spring and in the calendar years ( A comparison of mean data regarding initial capture dates during the two consecutive decades indicated that all 34 species arrived on average three days earlier from 1984-1993than from 1994-2003. However, the diff erence is not statistically signifi cant (Mann-Whitney U Test, U= 563, Z= 0.184, p = 0.854).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…In several species we found a signifi cant correlation between initial capture dates in the spring and in the calendar years ( A comparison of mean data regarding initial capture dates during the two consecutive decades indicated that all 34 species arrived on average three days earlier from 1984-1993than from 1994-2003. However, the diff erence is not statistically signifi cant (Mann-Whitney U Test, U= 563, Z= 0.184, p = 0.854).…”
Section: Resultsmentioning
confidence: 79%
“…Some of these can be attributed to the infl uence of global warming on avian spring migration, as shown by several studies (Bairlein and Winkel 2001;Sokolov 2001;Sparks et al 2001;Hüppop and Hüppop 2003;Butler 2003). Only the Orphean Warbler showed a strong positive correlation of initial capture with the calendar year, whereas the Barred Warbler and Grey Flycatcher displayed insignifi cant trends.…”
Section: Discussionmentioning
confidence: 84%
“…Temporal trends in factors such as average singing rates, that influence availability during a count, can also impart trends in count data unrelated to the true abundance. For example, there is increasing evidence that birds are breeding earlier now than in the past, presumably due to global warming (Butler 2003). Climatic trends that impart trends in the average singing rates of birds will bias abundance estimates over time unless analyses account for the temporal trends in detection probabilities.…”
Section: Factors Affecting Detection Probabilitiesmentioning
confidence: 99%
“…Moreover, FADs correlate positively with mean arrival date for species where the latter can be calculated Tøttrup et al 2006) and have been widely used to determine temporal change in migration (e.g. Sparks, 1999;Both and Visser, 2001;Butler, 2003;Cotton 2003;Sparks et al 2007). Analysis of FADs is particularly robust for analysing temporal change for the same population 72 (as here) (Tryjanowski et al 2005).…”
mentioning
confidence: 99%